Lack of clinical or haemodynamic rebound after abrupt interruption of beta‐blockers in patients with cirrhosis. Issue 9 (1st March 2016) - Payancé, A.; Bissonnette, J.; Roux, O.; Elkrief, L.; Gault, N.; Francoz, C.; Nekachtali, O.; Soubrane, O.; Lebrec, D.; Valla, D.; Durand, F.; Rautou, P.‐E.
Summary: Background: Beta‐blockers may have to be interrupted in patients with cirrhosis. The concept of a rebound after interruption of beta‐blockers is based on an animal study and on isolated case reports of variceal bleeding. Aim: To determine if a rebound occurs in patients with cirrhosis following abrupt interruption of beta‐blockers. Methods: We prospectively included all consecutive patients with cirrhosis undergoing right heart and hepatic vein catheterisation. Four groups were defined: 'no beta‐blockers' including patients not receiving beta‐blockers; '≤1 day', '2–3 days' and '≥4 days' classified according to the time patients had interrupted beta‐blockers before catheterisation. Results were expressed as median (interquartile range). Results: A total of 150 patients were included. Among the 25 patients in the groups '2–3 days' and '≥4 days', median duration of beta‐blockers interruption was 4 (3–6) days. No gastrointestinal bleeding occurred during that period, nor during the following month. Hepatic venous pressure gradient was not different among patients in usually treated with beta‐blockers. After adjustment, beta‐blockers interruption was not associated with hepatic venous pressure gradient. Cardiac index was higher in the '≥4 days' group [4.6 L/min/m 2 (3.5–5.1)] than in the '≤1 day' group [3.4 (2.6–4.0); P = 0.001] or in the '2–3 days' group [3.1 (2.7–3.7); P = 0.007], but not different from the 'no beta‐blockers' group. Conclusions: Abrupt interruption of beta‐blockers is associated neither with an apparent increase in the risk of variceal bleeding nor with a haemodynamic rebound. Thus, interruption of beta‐blockers in patients with cirrhosis may not require particular dosing or surveillance.